ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP EMOTIONAL RESPONSES DAN DAMPAKNYA KEPADA IMPULSE BUYING KONSUMEN DI MALL KOTA MALANG - Seno Aji Wahyono; Catharina Aprilia Hellyani; Evania Liana Marcos (Unitri Press, 2020)
Development in the retail industry continues to grow rapidly, especially in Indonesia, requiring retail companies to be able to bring out the differences or uniqueness of the company as a form defense. Retail companies in their efforts to attract consumers can provide an attractive and pleasant store atmosphere, so that consumers were expected to feel happy and interested in making purchase transactions. This aims to examining the effect of store atmosphere on emotional responses and their impact on consumer impulse buying in Malang city mall. This study uses the path analysis method that aims to determine the effect of store atmosphere on consumer emotions and the effect of store atmosphere on consumer emotions to impulse buying. Data collection was carried out by distributing questionnaires online to 200 respondents. The selection of respondents uses accidental sampling technique. Data collected from the distribution of questionnaires and analyzed by means of path analysis. From the results of this study it can be seen that Store atmosphere has a direct effect on Impulse Buying. Whereas Store atmosphere indirect effect on Impulse Buying with Emotional Responses as a moderate variable. It can be concluded that Emotional Responses strengthen the influence of Store atmosphere on Impulse Buying